RISK OF INTRODUCING HIGHLY DANGEROUS ANIMAL VESICULAR DISEASES INTO THE RUSSIAN FEDERATION - V. P. Semakina; T. P. Akimova; I. Yu. Solomatina; A. K. Karaulov (Ветеринария сегодня)
Animal vesicular diseases are rather widespread in the world. Transboundary vesicular diseases are mainly registered in African and Asian countries. They primarily include foot and mouth disease, sheep and goat pox, peste des petits ruminants, lumpy skin disease, swine vesicular disease, vesicular stomatitis, as well as relatively new Seneca Valley virus infection. The transboundary spread of vesicular diseases is mainly caused by legal and illegal movements of animals, animal products, feeds, live vaccines; migration of wild animals across the borders from neighboring countries and passive mechanical transmission of infection. The risk of vesicular disease agent introduction with legal import of live animals into the territory of the Russian Federation is minimal. Most likely, the causative agent can be introduced when livestock products are illegally imported from the following countries: China, Turkey, India, Mongolia, Iran, Kazakhstan, etc. Violations of foreign trade regulations pose a direct threat to the epidemic situation and economic security of Russia. There is a possibility of the introduction of vesicular agents with animal feed imports into the country since some viruses can potentially survive for a long time in some ingredients. Taking into account the fact that some neighboring countries are infected with vesicular diseases, the threat of infection introduction into Russia through migration of wild animals along the North Caucasian, Central Asian and Far Eastern routes still remains.